Empowering the Peripheral Ummah Through Waqf - Ismail, M. A.; Nik Ab Malik, N. M. A.; Mohd Shafiai, M. H. (Universiti Sains Islam Malaysia, 2024)
The peripheral ummah is the community that is excluded socially and economically from the market system. The inaccessibility to the market makes them poor which later creates the vicious and spiral problem of poverty. This study aims to propose a mechanism using waqf to eradicate the causes of the problem and let them be accessible to the market. Taking into consideration of altruist behaviour of other mainstream communities and good coordination between government and non-government organizations, waqf mechanism is proposed as source of fund to finance the actions to include the peripheral ummah into the mainstream community. The mechanism focuses on wealth creation activities. The waqf mechanism is effective as its characteristics are irrevocability, perpetuity and inalienability. Therefore, partial influence from the government or the community regarding the management of the waqf fund can be avoided.